Complementary effects of phosphorus supply and planting density on maize growth and phosphorus use efficiency - Gong, Haiqing; Xiang, Yue; Wako, Bilisuma Kabeto; Jiao, Xiaoqiang (Frontiers in Plant Science, 2022)
Phosphorus (P) supply and planting density regulate plant growth by altering root morphological traits and soil P dynamics. However, the compensatory effects of P supply and planting density on maize (Zea mays L.) growth and P use efficiency remain unknown. In this study, we conducted pot experiments of approximately 60 days to determine the effect of P supply, i.e., no P (CK), single superphosphate (SSP), and monoammonium phosphate (MAP), and different planting densities (low: two plants per pot; and high: four plants per pot) on maize growth. A similar shoot biomass accumulation was observed at high planting density under CK treatment (91.5 g plot–1) and low planting density under SSP treatment (94.3 g plot–1), with similar trends in P uptake, root morphological traits, and arbuscular mycorrhizal colonization. There was no significant difference in shoot biomass between high planting density under SSP (107.3 g plot–1) and low planting density under MAP (105.2 g plot–1); the corresponding P uptake, root growth, and P fraction in the soil showed the same trend. These results suggest that improved P supply could compensate for the limitations of low planting density by regulating the interaction between root morphological traits and soil P dynamics. Furthermore, under the same P supply, the limitations of low planting density could be compensated for by substituting MAP for SSP. Our results indicate that maize growth and P use efficiency could be improved by harnessing the compensatory effects of P supply and planting density to alter root plasticity and soil P dynamics.